Masters of cosmetic surgery, the video atlas the Dallas cosmetic model - Rohrich, Rod J.; Sinno, Sammy; Afrooz, Paul N. (Thieme, 2021)
"The rapid growth in global demand for cosmetic surgery has led to an urgent need for aesthetic surgeons to learn an ever-growing menu of advanced procedures. Masters of Cosmetic Surgery-The Video Atlas: The Dallas Cosmetic Model edited by internationally renowned plastic surgeon Rod J. Rohrich and esteemed colleagues Sammy Sinno and Paul N. Afrooz presents an amazing new method of learning cosmetic surgery techniques. The didactic video guide features contributions from the Who's Who of superb surgeons and dermatologists that are committed to excellence in their own practices and educational endeavors"--